A STUDY OF RESEARCH TRENDS IN LIBRARY AND INFORMATION SCIENCE IN THE UNIVERSITIES OF KHYBER PAKHTUNKHWA - Dr. Sajjad Ahmad1 Dr. Shehzad Ahmad , Sami Ullah, Muhammad Arshad (IJoLIS, 2024)
The study explores the research tendencies in the field of Library and Information Science (LIS) of the three universities in Khyber Pakhtunkhwa (KP), Pakistan during the period of 1983-2022. The data was collected through E-mail, Google scholar accounts, Whatsapp and personal contacts with the faculty members. The data of 392 publications (346 articles and 46 other publications) along with 1696 citations which these publications received was analyzed through bibliometric indicators.